PROPOSAL FOR BUSINESS PROCESS MAPPING USING BPMN: CASE STUDY IN A BRAZILIAN SHIPBUILDING INDUSTRY - Longaray, André Andrade (2017)
The present work aims to describe the use of Business Process Modeling Notation (BPMN) in the mapping of processes in a Naval and Offshore Construction company of the Naval Pole of Rio Grande, situated in Brazil. Methodologically, its purpose is a qualitative diagnostic study, whose design follows the guidelines of an action research, with the use of questionnaires and semi-structured interviews to collect data. Among the main results, it was possible to analyze the complete sequence of activities of the sector under analysis, which allowed verifying which processes would be more apt to the development of future improvements.